2015
DOI: 10.1093/jxb/eru513
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis response to low-phosphate conditions includes active changes in actin filaments and PIN2 polarization and is dependent on strigolactone signalling

Abstract: HighlightThis study provides an insight into the cellular events of cytoskeleton rearrangement, vesicle trafficking, and PIN protein localization that are associated with low-Pi response and are dependent on strigolactone-auxin cross-talk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 61 publications
(100 reference statements)
2
28
0
Order By: Relevance
“…PIN2 degradation in vacuoles is suppressed under phosphorus deficiency or treatment with phospholipase Dderived phosphatidic acid Membrane-localized PIN2 is degraded in the vacuole. Given that, under LP conditions, root hair elongation is reduced and auxin transport from the root tip to the shoot is blocked in pin2 seedlings but PIN2 expression is not significantly altered (Kumar et al, 2015;Bhosale et al, 2018), we examined the PIN2 degradation under both the NP and LP conditions. Indeed, observation of the fluorescence of PIN2-GFP fusion protein revealed the increased accumulation of PIN2 in the vacuole under NP conditions ( Fig.…”
Section: Pin2 Deficiency Results In Defective Root Hair Elongation Unmentioning
confidence: 99%
“…PIN2 degradation in vacuoles is suppressed under phosphorus deficiency or treatment with phospholipase Dderived phosphatidic acid Membrane-localized PIN2 is degraded in the vacuole. Given that, under LP conditions, root hair elongation is reduced and auxin transport from the root tip to the shoot is blocked in pin2 seedlings but PIN2 expression is not significantly altered (Kumar et al, 2015;Bhosale et al, 2018), we examined the PIN2 degradation under both the NP and LP conditions. Indeed, observation of the fluorescence of PIN2-GFP fusion protein revealed the increased accumulation of PIN2 in the vacuole under NP conditions ( Fig.…”
Section: Pin2 Deficiency Results In Defective Root Hair Elongation Unmentioning
confidence: 99%
“…Being, PINs polar localization in PM is primarily determined by the constitutive trafficking of PIN vesicles between the PM and endosomes which requires F-actin bundling. 40 Kumar et al 13 studied this and observed a significant reduction in the accumulation of BFA bodies, reduced movement of ARA7labeled endosomes and increased actin bundling under low Pi condition in WT but not in max2-1. In addition, mutants for MAX2, MAX4, PIN2 and TIR3 (required for polar auxin transport) and one ACTIN2 mutant line had a reduced response (in term of root hair density) to low Pi compared with WT.…”
Section: Sl-associated Root Development Involve Changes In Auxin Efflmentioning
confidence: 96%
“…Recently, Kumar et al 13 reported that SL signaling under low Pi condition (at least during early developmental stage, 48 hpg) transmits in a MAX2 dependent manner, 48 also involve regulation of PIN2 polar localization in PM and actin bundling and dynamics in Arabidopsis. In Kumar et al 13 studies, Arabidopsis seedlings under low Pi condition showed reduced PIN2 trafficking and polarization in the PM (similar to the results presented for PIN2 and 7 in Gonzalez-Mendoza et al 50 ), decreased ARA7labeled endosome trafficking, and increased actin filament bundling in root cells of WT. The max4-1, but not max2-1, with supplementation of synthetic SL (GR24) exhibited depletion of PIN2 from the PM under low-Pi conditions.…”
Section: Sl-associated Root Development Involve Changes In Auxin Efflmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis revealed that SLs inhibit bud growth by negatively regulating auxin transport in rice [156]. SLs regulate root development by inhibiting the transport of auxin from shoots to roots and auxin flux within root tissues, and regulate branching by affecting polar auxin transport (PAT)/canalization in rice [157][158][159]. When auxin is depleted, SL can inhibit bud outgrowth in pea.…”
Section: Sl or Kar Crosstalk With Auxinmentioning
confidence: 99%